Periodontite e perda dentária impactam negativamente a qualidade de vida relacionada à saúde bucal em portadores de doença renal crônica - Schöffer, Caroline (2024)
Patients with chronic kidney disease (CKD) have a high prevalence of periodontal disease and tooth loss compared to healthy individuals. Both conditions lead to difficulties in chewing, swallowing, tasting and speaking and therefore have functional and psychosocial consequences. Primary studies and systematic reviews that evaluate the impact of oral conditions on the oral health-related quality of life (OHRQoL) of this population are scarce and controversial. Therefore, the first study of the thesis is a systematic review, which aims to evaluate the impact of periodontal conditions on OHRQoL in patients with CKD. The selection of studies was carried out in the MEDLINE (via PubMed), EMBASE, LILACS, Web of Science, Scopus and DANS databases. Of the 1584 studies retrieved in the search, 7 were included. All studies presented moderate and high risk of bias and used the OHIP-14 instrument, with three simultaneously using the GOHAI. A meta-analysis demonstrated that OHIP-14 scores are higher in individuals with CKD compared to healthy controls (12.29 vs. 5.59), indicating impaired OHRQoL. Another meta-analysis showed that the prevalence of periodontitis in kidney patients was higher (71.4% vs 39.4%). Considering severity, renal patients with stage III/IV periodontitis scores were higher compared to those without periodontitis or with stage I/II periodontitis (4.49 vs 2.24). Furthermore, the pooled estimates showed a positive correlation between periodontal probing depth (r = 0.145; p = 0.028) and plaque index (r = 0.385; p < 0.001) with OHIP-14 scores. Therefore, despite the certainty of the evidence being very low, severe periodontitis, greater probing depths and plaque scores negatively influence the OHRQoL of patients with CKD undergoing regular hemodialysis therapy. The second study is a cross-sectional observational study that aimed to investigate the impact of tooth loss on OHRQoL in individuals with end-stage CKD (ESRD) and determine whether dialysis time (DT) modifies the effects of these associations. 180 adults with ESRD were evaluated by calibrated examiners. Oral examinations were performed for untreated tooth decay, periodontitis and tooth loss (TL) and OHRQoL was assessed using the OHIP-14 instrument. Tooth loss (RR = 1.56; 95% CI: 1.12 to 2.18) was associated with worse OHRQoL, with longer DT negatively modifying the effect of the association. It can be concluded that TL has an impact on OHRQOL in individuals with ESRD, with a greater effect among those with longer dialysis time.